Impact of oseltamivir on the risk of cancer - Chuang, Pei-Hua; Tzang, Bor-Show; Tzang, Chih-Chen; Chiu, Chun-Ching; Lin, Chun-Yu; Hsu, Tsai-Ching (Frontiers in Oncology, 2024)
Purpose: Mounting evidence has revealed the anti-cancer activity of various anti-viral drugs.Oseltamivir phosphate (OP), namely Tamiflu®, is routinely used to combat influenza infections.Although evidence has indicated the anti-cancer effects of OP in vitro and in vivo, little information is known about the effect of OP use on cancers in humans.: A nationwide population-based cohort study involving 13,977,101 cases with 284,733 receiving OP was performed to examine the association between OP use and cancers using the National Health Insurance Research Database in Taiwan between 2009 and 2018.The cohort study found that OP users showed a significantly lower incidence of lung cancer, colon cancer, liver, and intrahepatic bile duct cancer, oral cancer, pancreas cancer, esophagus cancer, stomach cancer, and prostate cancer. Additionally, OP users exhibited a lower risk of cancer-related Oseltamivir lowers liver cancer 2 mortality (adjusted HR=0.779; 95% confidence interval [CI] 0.743-0.817; p<0.001) and a reduced risk of developing liver cancer (adjusted HR=0.895; 95% CI 0.824-0.972; p=0.008), esophagus cancer (adjusted HR=0.646; 95% CI 0.522-0.799; p<0.001) and oral cancer (adjusted HR=0.587; 95% CI 0.346-0.995; p=0.048). Notably, OP users had a significant reduction in liver cancer occurrence over a 10-year period follow-up and a lower cancer stage at liver cancer diagnosis.These findings first suggest the beneficial effects and therapeutic potential of OP use for certain cancers, especially liver cancer.